Customer-driven business information provision in Malaysian government agencies’ library / Noor Zaidi Sahid - Sahid, Noor Zaidi (2017)
Ascertaining the customer needs and wants as well as delivering the desired satisfaction effectively and efficiently are the best ways of serving customers. In these circumstances, the credibility of the government is easily measured by the efficiency of its service delivery. Public sector managers, therefore, are under pressure to satisfy various stakeholders to increase efficacy, effectiveness and quality services, as well as achieve organizational goals and establish a culture of continuous improvements. The research aims to explore in-depth situations o f a customer-driven business information is being approached from the social constructionist orientation as well as engaging the interpretivist research paradigm. The research is based on the multiple case studies that involved twelve (12) librarians from twelve (12) selected libraries of the government agencies. To enter the perspectives of the respondents explicitly, the semi-structured interview was chosen to collect descriptive data of respondents. Responses have been analyzed thematically as it is proven to be a clear, step-by-step approach and flexible. It can correspond with a critical realism that could lead the researcher to analyze the unstructured data. The data were analyzed manually as it is more rigorous and transparent, hence they are interpreted more confidently. The findings of the study have implications for the model, policy, and practices on how customer-driven concept can be adopted by libraries and other government agencies. The research results demonstrate that the libraries of the government agencies involved in the study practices the customer-driven concept in the process of information provision. In terms of information category, this research has found three main types of business information, which are public information, proprietary information, and controlled information. Each category has specific users and is accessed differently. The findings have also successfully unlocked the questions on how the user-oriented concept is developed. The research contribution includes the development of a Customer-Driven Business Information Provision model. This model has been drawn up according to the perspectives of the libraries of the government agencies in Malaysia, employing two dimensions, i.e. the design and management of a customer-driven service system and the fostering of good governance. This model elicited five (5) themes of design and management of a customer-driven service system involving customer identification, customer needs surveys, service system design, service delivery, and service recovery. In this comprehensive model, the best practices of the libraries of the government agencies are empirically examined and can be used as guidance to the information providers that wish to establish customer-driven products or services.